(untitled) (Південний архів (історичні науки), 2022)
Purpose. The aim of the article is to analyze the book “Leaders of the Dnieper Insurgent Movement: a collection of documents”, published with the support of the South-Eastern Department of the Ukrainian Institute of National Memory. Methods. The author uses the method of scientific and logical criticism to analyze the author’s texts that supplement the collection of documents. The use of this method allows for a critical analysis of the author’s texts: introductory article, historical essay and archeographic preface. Results. It is established that the publication contains scientific novelty, as a significant part of the documents collected by O. Chepurko and Y. Pakhomenkov is introduced into scientific circulation for the first time. These materials contain 15 archival and criminal files of the leaders of the Dnieper insurgent movement, their brief biographical references. Much of the surnames were previously unknown to researchers. Organized documents make it possible to trace the methods of struggle of the punitive Bolshevik authorities against the insurgent movement in the Dnieper, to find out the attitude of the population to the members of the insurgent movement, to find out little-known facts. The authors outline the prospects for new research, modern interpretations and innovations in understanding the insurgency. Publications of future researchers of the period of liberation struggles and local historians. Сonclusions. Despite the critical remarks that are a mandatory element of any scientific criticism, the peer-reviewed work is a successful example of research work in archival institutions and is a valuable achievement of Ukrainian archeography of the Ukrainian Revolution of 1917–1921. The documents contained in the book open wide research perspectives for historians and local historians. The book was published with the support of the South-Eastern Department of the Ukrainian Institute of National Remembrance.